Satisfaction toward Blended Learning: A Pilot Study among Undergraduate Pharmacy Students in UniKL RCMP - Aina Amanina Abdul Jalil; Seow Lay Jing; Nur Najihah Izzati Mat Rani (Asian Journal of Medicine & Health Sciences, 2024)
The COVID-19 pandemic has prompted a shift towards blended learning, combining online and faceto-face elements in education. This study explores the impact of incorporating video creation as an assignment in the cosmeceuticals course among 38 undergraduate pharmacy students at UniKL RCMP. The objective is to assess students’ satisfaction and the effectiveness of video creation in enhancing their understanding of cosmeceutical concepts. This pilot study employs both qualitative and quantitative approaches and was conducted through the use of a questionnaire that contained both closed-ended and open-ended questions. The purposive sampling technique was used to collect the sample for this study. The survey instrument was a self-administer online questionnaire. The majority of the respondents expressed satisfaction with the video creation assignment, citing flexibility, enjoyment and engagement as key themes. Challenges included time constraints and technical issues for some students. Quantitative analysis indicates a significant positive impact on learning, with 68% feeling significantly enhanced understanding. The incorporation of video creation was deemed highly effective by 82% of students, while 18% found it somewhat effective. Overall satisfaction was high, with an average score of 8.61 out of 10. Despite challenges, the study concludes that incorporating video creation into assignments is a successful and well-received learning experience, supporting its continued integration into the educational curriculum. The findings contribute to the broader literature on blended learning and innovative pedagogical approaches, offering insights for educators, policymakers, and researchers aiming to enhance student learning outcomes.